Analisa Pengaruh Corporate Governance Terhadap Kinerja Intellectual Capital Melalui Capital Structure Sebagai Variabel Intervening - Nadya Gomes I; Saarce Elsye Hatane (Business Accounting Review, 2017)
The purpose of this research was to analyze either the direct influence of corporate governance to intellectual capital or the indirect influence of which that mediated by capital structure as the intervening variable. Corporate governance was measured by using board size, board composition and board meeting variables. Intellectual capital performance was measured by using value added intellectual capital method. Capital structure was measured by using leverage. This research was conducted on the companies in two sectors namely consumer goods and trade sectors, listed in Indonesian Stock Exchange during the period of 2010-2015 with a sample of 44 companies or 264 firm-year observation. Hypothesis testing was done by using multiple regression analysis with SPSS software version 20. The result revealed that for direct influence, only board size and board composition were significant in predicting VAIC. Only board composition and board meeting are significant in predicting leverage. Leverage is also found to be significant in predicting VAIC. But, for the indirect influence, leverage is not able to mediate the influence of board composition on VAIC.